2011
DOI: 10.1111/j.1747-0285.2011.01154.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Antimalarial Activity of Oxygenated 3‐alkylpyridine Marine Alkaloid Analogues

Abstract: A series of new oxygenated analogues of marine 3-alkylpyridine alkaloids were prepared from 3-pyridinepropanol in few steps and in good yields. The key step for the synthesis of these compounds was a Williamson etherification under phase-transfer conditions. All new compounds were evaluated for their antiplasmodial activity and cytotoxicity. A significant reduction in parasitaemia was observed for some of the prepared compounds, and the majority of them exhibited a selectivity index (SI) ranging from 2.78 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…In a recent work, some compounds of this type were assayed against Plasmodium falciparum (20). In this paper, some other analogues were tested against Leishmania species, and the results confirm the potential leishmanicidal activity of oxygenated marine alkaloids analogues.…”
mentioning
confidence: 71%
See 3 more Smart Citations
“…In a recent work, some compounds of this type were assayed against Plasmodium falciparum (20). In this paper, some other analogues were tested against Leishmania species, and the results confirm the potential leishmanicidal activity of oxygenated marine alkaloids analogues.…”
mentioning
confidence: 71%
“…Chemistry Compounds 5, 6, 7, 10, 12, 13, and 16 were synthesized as previously reported (20). The synthesis of the new 3-alkylpyridine compounds 8, 9, 11, 14, and 15 is depicted in Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although different classes of metabolites have been isolated from this group of marine sponges, these compounds are typically highlighted for their remarkable cytotoxic activity against tumor human cell lines [11,12], as are their analogs [14]. A small series of 3-APA analogs of theonelladine C (Figure 1) recently synthesized by our research group exhibited antiprotozoal activity [15,16] and pro-apoptotic action against a human colon carcinoma (RKO-AS-45-1) cell line [14]. We also observed that their cytotoxicity appeared to be affected by the alkyl chain length (9 or 12 carbon atoms) and the type of functional group attached to the end of this chain (e.g., azide or amine) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%